Peningkatan Hasil Belajar Siswa Menggunakan Model Pembelajaran STAD pada Materi Bangun Datar Kelas III SDN Babatan IV Surabaya - Aldi Setiadi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The purpose of this research is to improve students mathematics learning outcomes through the STAD type cooperative method. This research was conducted in class III at SDN Babatan IV Surabaya on two-dimentional figure as material. This research is a type of classroom action research. The research approach used in this research is a quantitative and qualitative approach. This classroom action research uses the Kemmis & Mc Taggart model. The samples taken were 35 students. The results of the research show that there is a significant influence between STAD (Student Team Achievement Division) on the learning outcomes of class III students at SDN Babatan IV Surabaya.